Aeration Strategies for the Removal of Iron From Water Manufacturing Industry - Edwinsyah, Riswan; Kahar, Kahar; Mulyati , Sri Slamet (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Clean water used for daily needs in the industry must meet health requirements and be safe to use, but artesian well water often contains various dangerous metals, one of which is iron. This study aimed to determine the effect of various variations in the length of aeration contact time on the reduction of iron content in water. In this study, the aeration process of water with various variations in the number of aerators was carried out to reduce the iron content. This type of research was experimental research with a pre and post-test design. The population and sample in this study were partially artesian well water in the shoe industry office. The sampling technique in this study used grab sampling. The results showed the greatest decrease in iron content was in 3 aerators with an initial iron content of 1.18 mg/l after treatment to 0.15 mg/l. The results showed that reducing iron content in clean water with variations in the number of aerators reduced Fe levels. It is recommended to the shoe industry to reduce the iron content of clean water by using an aeration process using an aerator with a capacity of 5 L/second. This study found that using aerators can be effectively used as an economical method in reducing iron content in the industrial and community environment.